Simultaneous Observation Data of GB-SAR/PiSAR to Detect Flooding in an Urban Area. (20th December 2009) - Watanabe, Manabu; Matsumoto, Masayoshi; Shimada, Masanobu; Asaka, Tomohito; Nishikawa, Hajime; Sato, Motoyuki
Abstract : We analyzed simultaneous observation data with ground-based synthetic aperture radar (GB-SAR) and airborne SAR (PiSAR) over a flood test site at which a simple house was constructed in a field. The PiSARσ ∘ under flood condition was 0.9 to 3.4 dB higher than that under nonflood condition. GB-SAR gives high spatial resolution as we could identify a single scattering component and a double bounce component from the house. GB-SAR showed that theσ ∘ difference between the flooding and nonflooding conditions came from the double bounce scattering. We also confirm that the entropy is a sensitive parameter in the eigenvalue decomposition parameters, if the scattering process is dominated by the double bounce scattering. We conclude thatσ ∘ and entropy are a good parameter to be used to detect flooding, not only in agricultural and forest regions, but also in urban areas. We also conclude that GB-SAR is a powerful tool to supplement satellite and airborne observation, which has a relatively low spatial resolution.